Sensing Qualia - Skokowski, Paul (Frontiers in Systems Neuroscience, 2022)
Accounting for qualia in the natural world is a difficult business, and it is worth understanding why. A close examination of several theories of mind - Behaviorism, Identity Theory, Functionalism, and Integrated Information Theory - will be discussed, revealing shortcomings for these theories in explaining the contents of conscious experience: qualia. Next, the possibility of information being either identical with experiential contents, or a foundation for building the universe from bits, will be considered and rejected. It will then be argued that in order to overcome the main difficulty of these theories - their failure to account for qualia - the senses should be interpreted as physical detectors. A new theory, Grounded Functionalism, will be proposed, which retains multiple realizability while allowing for a scientifically grounded program towards accounting for qualia in the natural world.